Dependence and Independence in Materials Design for EFL Teachers: An experimental study - HAMADA, Hacène (Journal of Human Sciences, 2013)
This paper deals with past and present issues related to materials design and development by Algerian teachers within pre-service and in-service experience of teaching English as a foreign language. The study is carried out among in-service teachers and pre-service (ENS students) teachers through an experimental method. It tests the validity of information processing (through learning styles and strategies) and discourse functions (through communicative language tasks) as independent variables which determine a number of design and development criteria as dependent variables. A pre-test, an experiment, and a post-test are used as research tools.